Pannexin 1 Modulates Axonal Growth in Mouse Peripheral Nerves - Horton, Steven M.; Luna Lopez, Carlos; Blevins, Elisabeth; Howarth, Holly; Weisberg, Jake; Shestopalov, Valery I.; Makarenkova, Helen P.; Shah, Sameer B. (Frontiers in Cellular Neuroscience, 2017)
The pannexin family of channels consists of three members – pannexin-1 (Panx1), pannexin-2 (Panx2), and pannexin-3 (Panx3) that enable the exchange of metabolites and signaling molecules between intracellular and extracellular compartments. Pannexin-mediated release of intracellular ATP into the extracellular space has been tied to a number of cellular activities, primarily through the activity of type P2 purinergic receptors. Previous work indicates that the opening of Panx1 channels and activation of purinergic receptors by extracellular ATP inflammation may cause inflammation and apoptosis. In the CNS (central nervous system) and PNS (peripheral nervous system), coupled pannexin and P2 functions have been linked to peripheral sensitization (pain) pathways. Purinergic pathways are also essential for other critical processes in the PNS, including myelination and neurite outgrowth. However, whether such pathways are pannexin-dependent remains to be determined. In this study, we use a Panx1 knockout mouse model and pharmacological inhibitors of the ATP-mediated signaling pathway to fill gaps in our understanding of Panx1 localization in peripheral nerves, roles for Panx1 in axonal outgrowth and myelination, and neurite extension. Our data show that Panx1 is localized to axonal, myelin, and vascular compartments of the peripheral nerves. Knockout of Panx1 gene significantly increased axonal caliber in vivo and axonal growth rate in cultured dorsal root ganglia (DRG) neurons. Furthermore, genetic knockout of Panx1 or inhibition of components of purinergic signaling, by treatment with probenecid and apyrase, resulted in denser axonal outgrowth from cultured DRG explants compared to untreated wild-types. Our findings suggest that Panx1 regulates axonal growth in the peripheral nervous system.